“This needs to be told to everyone”: Content analysis of written immediate responses from an online experiment examining health warning messages about alcohol consumption and breast cancer risk - Allison Anbari; Zachary Massey; Abigail Adediran; Na Wang; LaRissa Lawrie; Priscilla Martinez; Denis McCarthy (PLoS ONE, 2025)
Alcohol consumption increases breast cancer risk. We evaluated the responses of 748 United States female participants ages 21–29 to health warning messages addressing the relationship between alcohol consumption and increased breast cancer risk. In an online experiment, participants were randomly assigned to view standalone health warning messages about alcohol, breast cancer, and breast cancer health effects with varying picture and text attributes. Participants then completed post-message exposure assessments that included an immediate open-ended response to the message prompt. We conducted a qualitative content analysis of the responses and coded deductively based on constructs from the Message Impact Framework including message reactions, attitudes and beliefs, and behavioral intentions. These constructs and corresponding variables were present in participants’ responses. Response type did not vary by participants’ demographics or the attributes of the health warning message they viewed. The code new information was applied to 20% of the responses, indicating that those participants had no prior knowledge of alcohol and breast cancer risk. Alcohol and breast cancer messaging could impact drinking behaviors. Given the frequency of responses indicating a lack of awareness, more work in cancer prevention and population health messaging is warranted.